Budaya Organisasi Nilai Islam Good University Governance - Safitry, Martina; Irawati, Irawati; Murni, Sylviana (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This research aims to analyze the convergence between organizational culture, Islamic values, and the principles of Good University Governance (GUG) in the context of higher education review at the Institute of Social Sciences and Management STIAMI. As a non-profit organization oriented towards service provision and sustainability, higher education institutions have a unique need to implement effective governance. Specifically examining how Islamic values, particularly the prophetic leadership principles of Siddiq, Amanah, Fathonah, and Tabligh, can be integrated into the GUG framework to form a holistic and integrity-driven organizational culture. Through a descriptive qualitative methodology and a comprehensive literature review, this report outlines the definitions of organizational culture and GUG, identifies the essence of Islamic educational values, and presents a relevant integration model. The analysis of the perceptions of academics and higher education leaders provide regarding the implementation of Islamic values and GUG is also discussed, highlighting the existing challenges and opportunities. It was found that GUG in Higher Education requires a unique framework, where universal governance principles are enriched and redefined by fundamental Islamic values. This integration not only enhances operational efficiency but also strengthens ethical and spiritual integrity, fostering the creation of a productive and character-driven academic environment. In this paper, it concludes with strategic recommendations for strengthening the Islamic organizational culture and the effective implementation of GUG in higher education institutions. The novelty of this study lies in the development of an implementable SAFT-based governance model within the higher education context, particularly through a case study of STIAMI, which practices a unique 3I organizational culture: Ibadah (worship), Integrity, and Innovation. This study contributes to the literature by demonstrating that Islamic leadership principles serve not just as symbolic ideals but as practical instruments for establishing high-standard governance in modern Islamic educational institutions